2010
DOI: 10.1111/j.1574-6968.2010.01988.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of histone-like protein, Hlp, in Mycobacterium smegmatis dormancy

Abstract: The role of histone-like protein (Hlp) in the development of a dormant state in long-incubated stationary-phase Mycobacterium smegmatis cells was studied in two models: (1) adoption of 'nonculturable' (NC) state, which is reversible due to resuscitation with proteinaceous resuscitation-promoting factor (Rpf) and (2) the formation of morphologically distinct, ovoid resting forms. In the first model, inactivation of the hlp gene resulted in prolongation of culturability of starved cells followed by irreversible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Thus, H. pylori Hup protein appears to play a significant role in protecting its genomic DNA during stationary phase when toxic metabolites are accumulated. A similar role of a histone-like protein Hlp in Mycobacterium smegmatis was reported; Hlp is essential for cell viability while cells are at a dormant state (long-term stationary phase) [26]. A stationary phase survival defect was also observed for E. coli HU-like IHF mutant strain [27].…”
Section: Resultsmentioning
confidence: 54%
“…Thus, H. pylori Hup protein appears to play a significant role in protecting its genomic DNA during stationary phase when toxic metabolites are accumulated. A similar role of a histone-like protein Hlp in Mycobacterium smegmatis was reported; Hlp is essential for cell viability while cells are at a dormant state (long-term stationary phase) [26]. A stationary phase survival defect was also observed for E. coli HU-like IHF mutant strain [27].…”
Section: Resultsmentioning
confidence: 54%
“…DNA binding histonelike protein (hupB/Rv2986) ( Table 2) is capable of stabilizing DNA and prevents its denaturation under stress conditions (Enany et al, 2017). Previously it was found that HupB ortholog in Msm (Hlp) can provide compactization of the nucleoid during dormancy (Anuchin et al, 2010). It is interesting that a major protein found in the membrane fraction in D2 cells is Rv0341(iniB, Table 2) with unknown function that could also modify DNA topology due to its ability to interact with DNA (Shleeva et al, 2018) via a DNA-binding domain presented in the molecular structure according to Uniprot data base annotation.…”
Section: Resultsmentioning
confidence: 99%
“…H-NS, involved in the condensation of bacterial chromosome, could participate in the RecA-independent response mechanism in Rhodobacter sp., by bringing in close proximity two homologous region in a DNA molecule (Dame et al, 2000; Joyeux and Vreede, 2013). H-NS could also modify the nucleoid structure, acting as a physical shield protecting against DNA damage (Anuchin et al, 2010). H-NS protein was also found to be down-regulated (ratio = 0.6) in the UVA condition, which could indicate higher level of DNA damage induced by UVB compared to UVA radiation (Ravanat et al, 2001; Rastogi et al, 2010) thus demonstrating a high specificity in the response of Rhodobacter sp.…”
Section: Discussionmentioning
confidence: 99%